A Novel Insight into the Strain Effect of T2g Mode Splitting and Bandgap in Diamond. Issue 1 (25th October 2022) - Liu, Yonghui; Liu, Sheng; Robertson, John; Guo, Yuzheng
Abstract : Herein, a comprehensive analysis of the change in the bandgap and Raman frequency of diamond under the uniaxial strain along the [100], [110] and [111] directions using first‐principles calculation is presented. The results demonstrate that the triple degenerate T 2g mode splitting occurs spontaneously, owing to the strain‐induced symmetry breaking. Phonon splitting into two or three different modes demonstrates its anisotropy characteristics. The tensile softening and compressive stiffening of Raman frequencies depend on the bond length, bond angle, and bond strength response to the uniaxial strain. The bandgap decreases with increasing whether the tensile or compressive strain, which is attributed to the strain‐induced change of bond identities. These findings demonstrate that the uniaxial strain engineering has potential application in future diamond electronic devices. Abstract : The triple degenerate T 2g mode splitting of diamond occurs spontaneously, owing to the strain‐induced symmetry breaking. The tensile softening and compressive stiffening of Raman frequencies depend on the bond length, bond angle, and bond strength response to the strain. The bandgap decreases with increasing whether the tensile or compressive strain, which is attributed to the change of bond identities.